Development of MATLAB programs for electromagnetic analysis - Wang, Shiya (Nanyang Technological University, 2023)
The project involves testing the MATLAB programming of various electromagnetic equations. By combining the electric field integral equation (EFIE) with the method of moments (MoM), a simple and effective numerical method is explored to deal with the scattering problem from arbitrarily shaped surfaces. The scattering of electromagnetic waves on the surface of an object is a classical problem in electromagnetism. For arbitrarily shaped objects, numerical methods are usually required to solve the scattering problem due to complex boundary conditions. In this project, the application of the point-matching method to electromagnetic scattering is first investigated, followed by the selection of the RWG basis function for partitioning triangular surface facets to model the object. The surface scattering problem is solved by building MATLAB programs to simulate and calculate the surface current of the object. The electromagnetic analysis of several classical models of square plates, wires, cylinders and spheres are carried out under plane wave incidence based on both point-matching and RWG basis functions. In addition, this report presents a novel integral equation for the electric field by combining electrostatic and kinetic forces and introducing a new constant basis function. And the discretization and integral processes of this method are derived in detail, and a new impedance matrix is constructed, which is more reasonable and universal compared with the traditional EFIE.